The shape and volume restoration of the mammary glands in postoperative deformations - Lashchenko, M. V.; Sulik, V. V. (General Surgery, 2025)
This article is dedicated to modern methods of reconstructive and plastic breast surgery in women with postoperative deformities. Reconstruction of the mammary glands in cases of postoperative deformities relies on a variety of surgical techniques. The selection of an appropriate method depends on the morphological characteristics of the defect, tissue condition, prior surgical history, and the patient’s overall somatic status. The article highlights the anatomical and aesthetic parameters of the mammary glands, the classification of postoperative deformities, and modern approaches to secondary reconstruction (implants, autologous tissues, lipofilling), the importance of preserving or restoring the nippleareolar complex, as well as methods for objective measurement of breast shape and volume, including 3D scanning, magnetic resonance imaging (MRI), and mathematical models. The main approaches to reconstruction are discussed: implants, tissue expanders, autologous flaps (DIEP, TRAM, TDAP, SGAP, LICAP), and lipofilling as an additional or independent option for minor defects. Their advantages, disadvantages, and indications are analyzed. Special attention is given to breast symmetry, the influence of individual anatomical features of the patient, and the staging of surgical interventions. It is emphasized that early reconstruction after mastectomy contributes to better psychological rehabilitation, and the restoration of the breast’s aesthetic units improves patients’ quality of life. MRI is identified as the most accurate method for assessing breast volume, although less invasive and more accessible methods are preferred in routine practice. The article summarizes current approaches to the planning and execution of secondary reconstructive surgery for restoring breast shape, volume, and symmetry. The importance of an individualized approach is emphasized to achieve optimal aesthetic and functional outcomes.